Treatment of typical (enteropathic) hemolytic uremic syndrome - Bitzan, Martin; Schaefer, Franz; Reymond, Didier (Seminars in thrombosis and hemostasis, 2010)
Typical enteropathic HUS (eHUS) is triggered by Shiga toxin (Stx)-producing bacteria (STPB), predominantly Stx-producing ESCHERICHIA COLI O157. The cell biological aspects of Stx have been well defined, but host factors potentially predisposing to the development or severity of HUS remain elusive. Treatment of eHUS includes supportive measures and invasive extracorporeal therapies. Thirty to 60% of children with eHUS require dialysis. Peritoneal and hemodialysis appear equally effective. Patient age, center experience, and equipment availability determine the choice of the modality; circulatory instability may require continuous renal replacement therapies. At present, no evidence indicates that plasma infusion or exchange therapies improve outcome of Stx-induced HUS. However, the traditional separation between diarrhea-positive (D (+)) and negative (D (-)) HUS, implying two entirely different pathological pathways, requires a fresh look: Atypical HUS may follow nonspecific diarrhea, and, conversely, STPB and fecal Stx may not be detected anymore at the time of the diagnosis of HUS. Recently, Stx has been found to directly interfere with the alternative complement pathway regulator factor H in vitro, whereas some patients with Stx-HUS demonstrate evidence of complement activation. Among newer treatments for eHUS, development of Stx-neutralizing monoclonal antibodies is the most advanced. This review concludes with a discussion of the rationale, mode of action, and status of presently available therapeutic antibodies against Stx2 and Stx1.
Gesehen am 10.02.2023